2011
DOI: 10.1186/1471-213x-11-25
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-196a regulates bovine newborn ovary homeobox gene (NOBOX) expression during early embryogenesis

Abstract: BackgroundOocyte-derived maternal RNAs drive early embryogenesis when the newly formed embryo is transcriptionally inactive. Recent studies in zebrafish have identified the role of microRNAs during the maternal-to-embryonic transition (MET). MicroRNAs are short RNAs that bind to the 3' UTR of target mRNAs to repress their translation and accelerate their decay. Newborn ovary homeobox gene (NOBOX) is a transcription factor that is preferentially expressed in oocytes and essential for folliculogenesis in mice. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 54 publications
2
52
0
6
Order By: Relevance
“…Dysfunction and/or decrease in miRNAs of the miR-30 family could lead to podocyte apoptosis and depletion, glomerulosclerosis, and proteinuric renal disease. In other work, we found that the miR-30 family is expressed in renal tubular cells (J. Wu unpublished observations), and miR-196a was also shown to be expressed predominantly in the kidney (38). miR-196a was previously shown to correlate negatively with disease activity in SLE and has critical roles in cancer pathogenesis, viral immunity, and cell differentiation (39) as well as a role in kidney development.…”
Section: Discussionmentioning
confidence: 75%
“…Dysfunction and/or decrease in miRNAs of the miR-30 family could lead to podocyte apoptosis and depletion, glomerulosclerosis, and proteinuric renal disease. In other work, we found that the miR-30 family is expressed in renal tubular cells (J. Wu unpublished observations), and miR-196a was also shown to be expressed predominantly in the kidney (38). miR-196a was previously shown to correlate negatively with disease activity in SLE and has critical roles in cancer pathogenesis, viral immunity, and cell differentiation (39) as well as a role in kidney development.…”
Section: Discussionmentioning
confidence: 75%
“…The action of miRNAs on maternal mRNA degradation has been clear in Zebrafish embryos, which shows that the miR430 is abundant in the embryonic activation point, just at the moment the degradation of the maternal transcripts takes place (44) . Recent studies have shown that in the bovine, maternal mRNA as NOBOX and NPM2 are regulated under the action of the miR-181st and miR196a, respectively (104,105) . It is important to point out that the route of the degradation mediated by miRNAs is present only during the activation of the embryonic genome, and is absent during the oogenesis and in the initial stages of the embryo (47,52,54,106) .…”
Section: Maternal Effect On the Activation Of The Embryonic Genomementioning
confidence: 99%
“…La acción de miRNAs sobre la degradación de RNAm maternos ha quedado clara en embriones del Zebrafish, donde se observa que el miR430 es abundante en el punto de la activación embrionaria, justo en el momento en que sucede la degradación de los transcritos maternos (44) . Estudios recientes han demostrado que en el bovino, RNAm maternos como NOBOX y NPM2 son regulados bajo la acción de los miR-181a y miR196a, respectivamente (104,105) . Es importante señalar que la vía de degradación mediada por los of mice brg1-/-are arrested at the 2-4 cells stage (108) .…”
Section: Efecto Materno Sobre La Activación Del Genoma Embrionariounclassified
See 2 more Smart Citations